VD_FINDINFO HC / 2013 / 735 vom 11. September 2013 - VD Tribunal cantonal (2013)
RÉSILIATION, RÉSILIATION EN TEMPS INOPPORTUN, PROLONGATION DU BAIL À LOYER | 271 CO, 271a CO, 308 al. 1 let. a CPC (CH)